Implementasi Manajemen Perpustakaan dalam Meningkatkan Mutu Pendidikan Institut Teknologi Sawit Indonesia (ITSI) - Barus, Friska Anggraini; Purjianto, Purjianto; Isra, Marzuti; Sirait, Zulkarnain (IQRA`: Jurnal Perpustakaan dan Informasi, 2024)
In the world of education, the library is one aspect that works together as a facilitator in making the learning process a success. Library management (planning, organizing, budgeting, leadership and supervision) is one of the things requires attention so that library services are carried out effectively and efficiently. In line with the development of information technology, it is natural for libraries to be equipped with online scientific reading materials that are easily accessible to the academic community, especially students and lecturers, in order to optimally improve the quality of education. The quality of education in educational institutions will increase along with the availability of library information.This research was conducted to find out how to plan, implement and evaluate services at the Indonesian Palm Oil Institute’s library.This research uses qualitative methodology, where data is collected through observation, interviews and documentation studies. The research results show that: service planning in the ITSI Library begins with establishing the library’s vision and mission, which is in line with te vision and mission of its parent institution; work instructions are created as guidelines for the implementation of services; and service evaluation is carried out internally with the participation of the academic community.